Tetra Helix: Collaborative Power as A Character Education Support System Pandemic - Rahmat, Rahmat; Sapriya, Sapriya; Tanshzil, Sri Wahyuni; Rendra, Agus (International Journal Pedagogy of Social Studies, 2021)
The pandemic has widened the barrier to character decline in education. Modified learning through online stops various character education approaches that are carried out directly in face-to-face. The purpose of this study is to describe the role of the collaboration of four parties (Tetra helix) which encourages the implementation of character education during the pandemic. Through a mix design approach with the parallel convergent method, a research was carried out involving 70 respondents from school principals, teachers, committees, parents and students. The results of the Tetra Helix collaboration encourage the implementation of various character education activities such as programs capacity building through project-based learning innovations, programs share to care, and parenting. The role of the tetra helix collaboration is carried out starting from planning,implementing to evaluating character education in schools.